March 8, 2019: A snapshot of new participants in the feminist mobilisation - Maite Aurrekoetxea-Casaus (Papers)
This article explores a “new feminist subject” in the context of the mobilisation for Women’s Day (8 March 2019) in the city of Bilbao. Through a convergent quantitative–qualitative design methodology, issues relating to feminist identity and elements connected to neoliberalism that make up the feminist movement were addressed. The objective was to detect the new elements or nuances of neoliberal ideology that converge in the identity of the women who participated in the social protests and organisations linked to feminism. Among the participants in the M8 protests, the existence of new neoliberal indicators in women who call themselves feminists is verified. This article’s contribution is thus essential to understand the current establishment and explosion of feminist activism and the ideological overtones of new participants in feminist activism. Future research will shed light on the persistence or consolidation of this neoliberal drift in the feminist movement.